Design of a Mobile-Based Online Guitar Learning Platform Using the Agile Method - Kevin Octavianus Manurung (Yayasan Kita Menulis, 2026)
This study aims to design a mobile-based online guitar learning platform using the Agile method. The background of this research is the high public interest in learning guitar, alongside the lack of structured and beginner-friendly learning media. Agile was chosen for its flexibility, iterative process, and focus on continuous user feedback. The platform was developed using Flutter and includes key features such as basic guitar materials, video tutorials, interactive practice via a virtual fretboard, and a feedback form for questions and suggestions. Testing results show the application runs smoothly, is responsive, and is user-friendly for beginners. This platform is expected to make guitar learning more effective, structured, and enjoyable, and to contribute positively to the development of digital music education.